2014
DOI: 10.1104/pp.113.231993
|View full text |Cite
|
Sign up to set email alerts
|

Posttranslational Modification of Maize Chloroplast Pyruvate Orthophosphate Dikinase Reveals the Precise Regulatory Mechanism of Its Enzymatic Activity

Abstract: In C 4 plants, pyruvate orthophosphate dikinase (PPDK) activity is tightly dark/light regulated by reversible phosphorylation of an active-site threonine (Thr) residue; this process is catalyzed by PPDK regulatory protein (PDRP). Phosphorylation and dephosphorylation of PPDK lead to its inactivation and activation, respectively. Here, we show that light intensity rather than the light/dark transition regulates PPDK activity by modulating the reversible phosphorylation at Thr-527 (previously termed Thr-456) of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
38
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 56 publications
(72 reference statements)
1
38
0
Order By: Relevance
“…3B) is consistent with PPDK phosphorylation playing a pivotal role in the LD temporal coordination of CAM, and correlates with the LD dephosphorylation/phosphorylation of PPDK during C 4 photosynthesis (Burnell and Chastain, 2006;Chen et al, 2014). However, to our knowledge, this is the first report of LD phosphoregulation of PPDK in a CAM species.…”
supporting
confidence: 77%
“…3B) is consistent with PPDK phosphorylation playing a pivotal role in the LD temporal coordination of CAM, and correlates with the LD dephosphorylation/phosphorylation of PPDK during C 4 photosynthesis (Burnell and Chastain, 2006;Chen et al, 2014). However, to our knowledge, this is the first report of LD phosphoregulation of PPDK in a CAM species.…”
supporting
confidence: 77%
“…Phosphorylation and dephosphorylation of residue Thr-527 of PPDK lead to its inactivation and activation, respectively. This process is accomplished by a single, bifunctional protein, namely PPDK regulatory protein (PDRP; Burnell and Hatch, 1985), and the process is light intensity dependent (Hatch and Slack, 1969;Chen et al, 2014b). PDRP is an unusual enzyme in three respects.…”
mentioning
confidence: 99%
“…After Fukayama et al (2001) firstly reported the existence of an internal PPDK regulatory protein (PDRP) in rice, Chastain et al (2002Chastain et al ( , 2006 confirmed that PPDK underwent a rapid, posttranslational down regulation in activity via PDRP catalyzed Thr527 phosphorylation of PPDK in developing rice grains. Recently, Chen et al (2014) found that Ser528 was another target of PDRP. But it is not as important as Thr527 in phosphorylation because of the space steric effect.…”
Section: Discussionmentioning
confidence: 99%
“…It is a bifunctional protein that catalyzes both PPDK inactivation (phosphorylation) and activation (dephosphorylation) (Chastain and Chollet, 2003). The most recent research shows that changes in light intensity, rather than light/dark transition, regulates the activity of PPDK in maize (Zea mays) leaves via reversible phosphorylation at Thr527 (Chen et al, 2014).…”
Section: Introductionmentioning
confidence: 99%